2011
DOI: 10.1021/jp109895c
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational and Electronic Spectroscopy of the 4-Hydroxystyrene−CO2 Cluster and Its Hydrate: A para-Coumaric Acid Impostor

Abstract: We report on the results of high-resolution spec-troscopic studies on the 4-hydroxystyrene-CO(2) cluster. We show that these clusters are generated upon heating of para-coumaric acid, the chromophore of the photoactive yellow protein (PYP), as the result of a thermal decarboxylation process. Since the mass of the cluster and the starting material are the same, standard mass-resolved multiphoton ionization spectroscopic methods do not suffice to distinguish these clusters from para-coumaric acid. Instead, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Gas-phase studies of pCA have for a long time not been possible. [11][12][13] Recently, we succeeded in recording the rst excitation and absorption spectra under supersonic beam conditions. These studies enabled the identication of the lowest electronically excited state and the geometry changes associated with electronic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase studies of pCA have for a long time not been possible. [11][12][13] Recently, we succeeded in recording the rst excitation and absorption spectra under supersonic beam conditions. These studies enabled the identication of the lowest electronically excited state and the geometry changes associated with electronic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugate base of para -coumaric acid ( p- CA, HO–C 6 H 4 –CHCH–COOH) has been under substantial experimental and theoretical study because it is considered to be a model system for the chromophore in the photoactive yellow protein (PYP). , In the protein, the anionic chromophore is embedded in a hydrophobic pocket where it is covalently linked to a Cys residue by a thio-ester bond replacing the carboxylic OH of p -CA . Spectroscopic studies on PYP in solution revealed that the absorption maxima closely match those of the gas-phase chromophore .…”
mentioning
confidence: 99%
“…This discrepancy was suggested to arise from complications in generating the mass-spectrometrically indistinguishable phenoxide and carboxylate precursor ions. Molecular-beam UV spectroscopic studies on neutral p- CA showed that a (mass-spectrometrically indistinguishable) ‘impostor’ can readily replace the ‘elusive’ PYP chromophore during its transfer to the gas phase. To avoid ambiguities in the deprotonation site of p- CA, methyl-derivatives can provide isomer specificity, although even studies such as these are not always unambiguous. , Adequate knowledge of the isomeric structure of p -CA in the gas phase and its dependence on ESI conditions is essential to interpret experimental and theoretical investigations of its photochemical properties.…”
mentioning
confidence: 99%